A Restless Embrace of the Past? The Conference on Russia Papers 2022 - Šrāders, Sandis; Terry, George Spencer (University of Tartu Press, 2022)
The Baltic Defence College's "Conference on Russia Papers 2022: A Restless Embrace of the Past?" begs a question. How will Russia's past shape its present and future, both at home and abroad? This volume's chapters include a wide range of Russian-related topics organized into four main subject groups. The first of these categories is Russian views, with a focus on tendencies toward militarism, Russian understandings of international order, and the effects of COVID-19 on policy. The following subject is about power dynamics and perceptions, with a focus on Russia's contingent power structures, Russian narratives, and future projections. The third theme centers on the Baltic region's connection with Russia, investigating Russia's influence and information warfare from many angles. Finally, the concluding section examines Russian interests around the world, analyzing the position of Belarus', Russia's options globally, and the potential of a grand vision of Russian foreign policy. The volume concludes by highlighting the challenges of maintaining dialogue in light of recent trends, particularly in the last half decade and especially in the last several months.